Modificaciones en el ángulo SN-Frankfort en los distintos biotipos faciales en pacientes de ortodoncia en consultorio privado de Iquitos - Cabellos Tuesta, Cidlia Eschancennahar (2022)
The objective of the present study is to evaluate the modifications of the SN-FRANKFURT angle in the different facial biotypes. The study was quantitative, no experimental, observational, cross-sectional and correlational. The population consisted of 80 patients who were treated at the private clinic in the city of Iquitos. And the sample consisted of 80 lateral cephalometric radiographs of these patients. Results: 70.9% of patients were Dolicofacial and 29.1% Mesofacial; there was no Brachyfacial. 92.4% of the sample had an SN-Frankfort angle of less than 7°; 2.5% had an angle of 7°; and 5.1%, an angle greater than 7º. Of the total Mesofacial the highest percentage had an angle of less than 7° with 27.8%; the highest percentage of Dolicofacials had an angle of less than 7° with 64.6%. Only 2.5% of the sample had an angle of 7° and were Dolicofacial. 5.1% had an angle greater than 7°. Conclution: No relationship was found between facial biotype and SN-Frankfort angle (p = 0.718).